Episodic memory training with emphasis on categorization for older adults without dementia and depression / Treino de memória episódica com ênfase em categorização para idosos sem demência e depressão - Fabiana Castillo Roda Carvalho; Anita Liberalesso Neri; Mônica Sanches Yassuda (Psicologia: Reflexão e Crítica, 2010)
Aging may lead to cognitive changes, especially in memory. Yet, research suggests that older adults may improve memory performance after training. The present study aimed at evaluating the effects of episodic memory training offered to healthy Brazilian older adults. Fifty seven participants were randomly divided into control group (COG = 26) and experimental group (EXG = 31). The EXG participants completed a pre-test, five sessions of episodic memory training in which they were instructed to categorize grocery lists and pictures, and a post-test. Results indicated that episodic memory training involving learning and practice with categorization promoted significant improvement in episodic memory performance and in better using the trained strategy.